A single-seed uniform distribution and spreading device for real-time detection of Ambrosia artemisiifolia and Ambrosia trifida seeds in imported soybeans - Liu, Ze; Qiao, Xi; Qiang, Jianwei; Zhang, Shuo; Tian, Zhihui; Gu, Yujuan; Chen, Jun (Frontiers in Plant Science, 2025)
China relies heavily on imported soybeans due to insufficient domestic production, but these imports are often contaminated with quarantine weed seeds such as A. artemisiifolia and A. trifida. The introduction of these species poses serious ecological risks, highlighting the urgent need for reliable real-time detection methods. In this study, a single-seed uniform distribution and spreading device was designed to minimise occlusion and ensure consistent seed visibility. The device integrates a parabolic seed-socket distribution unit with an embedded system. After seeds were arranged in a single layer on a conveyor belt, a detection camera captured images that were processed by the YOLO_P2 model for seed recognition and counting. Device performance was optimised using the Taguchi experimental design, and evaluated with signal-to-noise ratio, mean, and variance. Experimental analysis revealed that the speeds of the seed-spreading roller and conveyor motor were the most significant factors affecting distribution uniformity. Validation experiments showed that the optimised system achieved detection accuracies of 95.73% for A. trifida and 94.41% for A. artemisiifolia, with an average processing time of 7.6 minutes per sample. These results demonstrate that the proposed device provides a practical, cost-effective solution for quarantine inspection, combining high-throughput capability with real-time performance to support ecological protection efforts.